Caregivers’ Knowledge and Attitude on Breastfeeding Practices and its Influence on Primiparous Mothers - Mathema, Smriti; Shrestha, S; Pokhrel, M (Nepal Medical College Journal, 2020)
The role of primary caregiver is crucial in the mother’s continuity of care and in improving the health of families by supporting breastfeeding. A comprehensive understanding of the relationship between caregiver knowledge of breastfeeding and its influence on the mother has not been established. Findings from this study hope to provide improvisation of existing breastfeeding programs to include advocacy, counselling and training of caregivers. This study was a cross-sectional, correlation study of the level of knowledge of caregivers about breastfeeding and its influence on primiparous mothers. The participants were recruited from a tertiary hospital located in Kathmandu and a one-one face-to-face interview using a self-constructed structured questionnaire was conducted in the postnatal and private ward where the patients were admitted. A total of 238 caregivers of primiparous mothers participated in this study. The collected qualitative data were then analyzed with descriptive statistics. Most of the primary caregivers who were interviewed were mothers of the patient (30.2%), followed by other relatives (22.3%), spouse (21.4%), mother-in-law (20.2%) and siblings (5.9%). Among the 238 participants, it was found that the level of caregiver’s knowledge of breastfeeding was low in 74 (31%), moderate in 128 (54%) and good in 36 (15%). Overall, the study showed a fairly inadequate knowledge towards various correct breastfeeding practices. There is a huge gap in knowledge and an urgent need to include primary caregivers of pregnant women in counselling and training of breastfeeding practices in order to improve infant health.